First Department for Foreign Students, Beijing Languages Institute, A Practical List of Commonly Used Chinese Words for Foreigners, Beijing, 1981, 130 pp. - Maeth Ch., Russell; Quartucci, Guillermo (Estudios de Asia y África, 1983)
-